Complete Sequences of the Velvet Worm Slime Proteins Reveal that Slime Formation is Enabled by Disulfide Bonds and Intrinsically Disordered Regions. Issue 18 (18th May 2022) - Lu, Yang; Sharma, Bhargy; Soon, Wei Long; Shi, Xiangyan; Zhao, Tianyun; Lim, Yan Ting; Sobota, Radoslaw M.; Hoon, Shawn; Pilloni, Giovanni; Usadi, Adam; Pervushin, Konstantin; Miserez, Ali
Abstract: The slime of velvet worms (Onychophora) is a strong and fully biodegradable protein material, which upon ejection undergoes a fast liquid‐to‐solid transition to ensnare prey. However, the molecular mechanisms of slime self‐assembly are still not well understood, notably because the primary structures of slime proteins are yet unknown. Combining transcriptomic and proteomic studies, the authors have obtained the complete primary sequences of slime proteins and identified key features for slime self‐assembly. The high molecular weight slime proteins contain cysteine residues at the N‐ and C‐termini that mediate the formation of multi‐protein complexes via disulfide bonding. Low complexity domains in the N‐termini are also identified and their propensity for liquid‐liquid phase separation is established, which may play a central role in slime biofabrication. Using solid‐state nuclear magnetic resonance, rigid and flexible domains of the slime proteins are mapped to specific peptide domains. The complete sequencing of major slime proteins is an important step toward sustainable fabrication of polymers inspired by the velvet worm slime. Abstract : Combining transcriptomic and proteomic studies, the full‐length sequences of proteins forming the sticky slime of the velvet worm are obtained, revealing the presence of cysteine residues mediating the formation of disulfide‐bonded multi‐protein complexes, as well as low‐complexity sequences exhibiting liquid‐liquid phase separation. The presence of β‐sheet domains is also predicted and detected in the slime by solid‐state NMR.